Balinese Endek Woven in the Framework of Indonesian Diplomacy at the G20 Summit - Putu Ratih Kumala Dewi (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This research aims at examining the implications of culture in international relations with regard to the contemporary political economy by analyzing Indonesian strategies in introducing the Balinese Endek woven creative industry at the 2022 G20 Summit. In this context, cultural diplomacy theory, which includes the concept of soft power, and the creative economy was adopted. Primary data was obtained through interviews conducted with representatives from the Department of Culture of Bali Province, as well as artisans specializing in the craft of Catri Endek woven using qualitative methods. Meanwhile, secondary data was collected through related literature and official government websites. The appearance of Balinese Endek woven at the G20 Summit could be studied through three paradigms, namely social, political, and economic dimensions. The socio-political paradigm of national interests was supported by soft power by introducing Balinese Endek woven as part of Indonesian culture by targeting the public. From an economic perspective, cooperation and the Indonesian economy could be increased.